THE EFFECT OF WORK – LIFE BALANCE, JOB SATISFACTION AND WORK STRESS ON TURNOVER INTENTION AT EMPLOYEES OF PT PELAYARAN AGUNG SAMUDRA KETAPANG – BANYUWANGI - Pristiwantiyasih Pristiwantiyasih; Happy Adianita; Edy Suhartono (Jurnal Ekonomi, 2022)
PT Pelayaran is a company that provides sea transportation services for service users who need it. This study aims to examine the effect of work-life balance variables, job satisfaction and job stress on turnover intention, either partially or simultaneously. The sample in this study amounted to 43 respondents who were all employees of PT Pelayaran Agung Samudra Ketapang – Banyuwangi. Collecting data in this study using observation, interviews, distributing questionnaires and documentation. Measurement of the questionnaire used a 4-point rating scale to measure 12 questions. Processing data in this study using SPSS 25 with a random sampling technique using the slovin formula. The results of this study indicate that work – life balance, job satisfaction and job stress simultaneously affect turnover intention with an Fcount of 8.729. Work – life balance partially has a significant negative effect on turnover intention with a tcount of -0.267, job satisfaction partially has a negative effect on turnover intention with a tcount of -1.260, work stress partially has a positive effect on turnover intention with a t-value of 3.553. So that in this study work stress is the most dominant variable affecting turnover intention based on the comparison of the t-value of the three variables.